Colorimetric determination of serum acid phosphatase activity using adenosine 3′-monophosphate as substrate - Ellis, Graham (1971)
The hydrolysis of adenosine 3′-monophosphate by serum acid phosphatase has been coupled to the liberation of ammonia from the adenosine generated through the action of exogenous adenosine deaminase. The ammonia is measured at the end of the incubation by a modification of the phenol-hypochlorite reaction of Berthelot. Optimum conditions for the enzyme reaction have been defined. Inhibition of the Berthelot reaction by the serum used in the assay is small, and may be compensated by a correction factor. Although the value for the control is high in relation to the test over the normal range, this is largely outweighed by the good sensitivity and precision of the method. The substrate is not significantly hydrolysed by erythrocyte acid phosphatase within the limits encountered in haemolysed sera. Experience of the method in routine hospital diagnosis compared favorably with that of a standard method employing disodium phenyl phosphate as substrate. It is suggested that activities greater than 3·1 IU/l should be further investigated and those greater than 3·7 IU/l should be regarded as definitely raised. The stability of human serum AcPase when promptly separated and held at 4°C or − 20°C was confirmed. At room temperature, acidification to pH 6·0 greatly improved stability.